Analysis of Concept Construction and Student Errors on the Topic of Double Integral Based on APOS Theory - Yarman, Yarman; Yerizon, Yerizon; Dwina, Fitrani; Murni, Dewi; Hevardani, Kelly Angelly (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Integral learning is particularly challenging for students, primarily due to misconceptions predominantly caused by students' lack of understanding about functions, limits, and derivatives. Therefore, this research aims to investigate students’ thinking processes when solving double integral using Action, Process, Object, and Schema (APOS) theory, with a focus on past errors. In order to achieve the objective, a descriptive qualitative method was adopted. Data was collected from tests, interviews, and relevant documentation, and tested for validity using triangulation methods. The obtained results showed that high-ability students understood APOS stages in solving double integral. However, at the object stage, a lack of thoroughness in simplifying algebra led to misunderstandings. Medium-Ability Student (MS) was observed to successfully reach APOS stages when solving double integral using polar coordinates. Low-Ability Student (LS), on the other hand, showed inadequate understanding at the process stage, as evidenced by the failure to correctly draw the area and set integral boundaries. During the course of this investigation, process errors were found to be commonly associated with the calculations of double integral. In order to address these issues, Genetic Decomposition (GD) should be designed for other calculus topics, and error classification expanded to enhance the effectiveness of lectures.